2018
DOI: 10.21475/ajcs.18.12.12.p942
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll content, water relation traits and mineral ions accumulation in soybean as influenced by organic amendments under salinity stress

Abstract: The pot experiment was conducted to assess the effect of organic amendments to improve leaf chlorophyll and water content as well as mineral ions accumulation in BARI soybean 5 under saline condition. Two types of organic amendments i. water hyacinth compost ii. rice husk biochar were mixed in soil at 5 tha-1 and 10 tha-1 of both. Irrigation was done with 50 and 100 mM saline solution from 14 th days after sowing (DAS) to maturity, where control plants were irrigated with tap water. Data on chlorophyll content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In terms of soil fertility and productivity, organic manures are superior to inorganic fertilizers because they improve soil health by improving physical, biological and chemical properties of soil [4][5][6][7][8] which result in higher yield and better-quality crop [9]. Moreover, application of organic amendments not only enhance the crop production but also can ameliorate soil salinity [10][11][12]. But higher crop yield will not be attained by sole supply of organic manures because of lower amount of nutrients to meet the crop requirement [13].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of soil fertility and productivity, organic manures are superior to inorganic fertilizers because they improve soil health by improving physical, biological and chemical properties of soil [4][5][6][7][8] which result in higher yield and better-quality crop [9]. Moreover, application of organic amendments not only enhance the crop production but also can ameliorate soil salinity [10][11][12]. But higher crop yield will not be attained by sole supply of organic manures because of lower amount of nutrients to meet the crop requirement [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other types of ameliorant such as water hyacinth compost and rice husk biochar have a positive effect in mitigating the negative impact of salinity on soybean plants. [40].…”
Section: Yield and Yield Attributesmentioning
confidence: 99%
“…Shoot water content and leaf water potential were decreased by salinity [68]. Ferdous et al [69] conducted an experiment with soybean under salt stress and found that RWC was decreasing with increasing salinity levels. The control treatment showed 89% RWC and it reduced to 73% at 100 mM salinity level.…”
Section: Water Relationmentioning
confidence: 99%